Editorial: Watching My Mother Die - Subjectivity and the Other Side of Dementia - Nancy J Moules (University of Calgary, 2018)
In this editorial, the authors discuss the idea of subjectivity as an often levelled criticism of qualitative reasearch, challenging the binary divide between subjective and objective. As an example of what could be "accused" of being a subjective account, Moules then discusses her experience of being at the other end of her mother's recent encounter with dementia.